Bicamada polarizada de gás de elétrons bidimensional sob ação de um campo magnético no plano - Oliveira, Leylanne Dayse (2020)
We have analytically investigated the electronic properties of a two-dimensional electrongas (2DEG) confined in a coupled bilayer system, i.e. two 2DEG layers, under the elect ofan in plane magnetic field and out-of-plane electric field. Such bilayer 2DEG-like systemsare very interesting quantum systems and were widely studied in the past decades dueto many possible phenomena in connection with the tunneling between the two 2DEGlayers, in a similar way as in double quantum well structures with an additional electronicdegree of freedom in the growth direction. By solving the 2 x 2 Schrodinger Hamiltonian, with the (off-) diagonal terms describing the top and bottom 2DEG layers (the couplingbetween the layers), we calculate the energy spectrum for difierent system configurationsand discuss the eleects of external electric and magnetic fields, as well as the consequencesof coupling term on it. Within this two-band effective mass approximation, one also consi-ders that the two layers are twisted with respect to each other and that they can be formedby different anisotropic semiconductors, i. e. with different effective masses along the xand y directions in each 2DEG layer. We show that: (i) the coupling energy term betweenthe layers breaks the degeneracy of the states; (ii) the presence of an in-plane magneticfield causes a linear transverse shift in momentum, i. e. the energy levels correspondingto different 2DEG layers are shifted in opposite directions in the wave-vector space, whichleads to the (anti-) crossing of the energy dispersion curves when the coupling term is(not) taking in account; (iii) in the presence of both electric and magnetic fields, one canobserve a distortion of the two energy branches with a formation of a two-valley struc-ture with different Fermi surfaces.